Hybrid System Analysis and Control of a Soft Robotic Gripper with Embedded Proprioceptive Sensing for Enhanced Gripping Performance. (22nd March 2021) - Park, Myungsun; Jeong, Bomin; Park, Yong-Lae
Abstract : Soft Grippers In article number 2000061, Yong‐Lae Park and co‐workers present a method of controlling a soft robotic gripper for grasping unidentified objects using a hybrid system analysis approach, which enables the system to detect the size of the object and to determine the optimal position of the gripper for successful grasping based on the proprioceptive feedback from an embedded soft strain sensor.